Effects of nitrogen fertilization on the fate of high-risk antibiotic resistance genes in reclaimed water-irrigated soil and plants - Cui, Erping; Zhou, Zhenchao; Cui, Bingjian; Fan, Xiangyang; Ali Abid, Abbas; Chen, Taotao; Gao, Feng; Du, Zhenjie (Environment international, 2024)
[Display omitted] •Nitrogen type rather than application rate dominated high-risk ARGs increase in soil.•NO3–-N and NH4+-N treated soil had lower ARGs abundance than CO(NH2)2 treated soil.•Bacterial community mainly drove ARGs variation in soil–plant system.•NH4+-N fertilizer was proposed to control ARGs spread in reclaimed water irrigated soil–plant. High-risk antibiotic resistance genes (ARGs) in reclaimed water-irrigated soil pose a potential threat to ecosystem and human health. Inorganic fertilization – including with nitrogen, a key ingredient in agricultural production – may affect the ARG profile in soil. However, little is known about nitrogen fertilization's influence on ARGs profiles in the soil–plant system. This study investigated the effects of different nitrogen fertilizer types (CO(NH2)2, NO3–-N (NaNO3) and NH4+-N (NH4HCO3)) and different nitrogen fertilizer application rates (low, medium, high) on the distribution of high-risk ARGs in reclaimed water-irrigated soil and plants using quantitative PCR, high-throughput sequencing and metagenomic sequencing. Soil microcosms results revealed that nitrogen fertilization significantly affected the pattern of high-risk ARGs in soil, and also affected high-risk ARGs abundance and transfer capacity in plants. Compared with nitrogen fertilizer application rate, nitrogen fertilizer types significantly contributed to enhancing the soil resistome, with the order of CO(NH2)2 > NO3–-N ≈ NH4+-N. The medium application of NO3–-N and NH4+-N significantly reduced high-risk ARGs abundance in the leaf endophyte. Bacterial community mainly drove the variation of ARGs in nitrogen-fertilized soil–plant system, and class I integron and metal resistance genes (MRGs) also had direct effects on these high-risk ARGs. A similar high-risk ARGs pattern was also found in field plot experiments, and several dangerous pathogens were observed as the main high-risk ARGs potential hosts in nitrogen-fertilized soil. Based on an economic assessment, application of NH4+-N (NH4HCO3) could reduce costs by $1,312.83 ha−1 compared with NO3–-N (NaNO3). These results showed that the more important role of nitrogen type might be an effective and economical way to control high-risk ARGs spread in soil–plant system under reclaimed water irrigation.